2015
DOI: 10.1002/jmri.24988
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between MRI T1rho value and histological findings of intact and radially incised menisci in microminipigs

Abstract: Zonal variations of the T1 rho value were observed in intact menisci due to varying structure in each zone. T1 rho values were correlated with histological changes such as collagen fiber organization and safranin-o stainability in incised menisci. This study supports T1 rho mapping as useful for evaluating ultrastructural composition in menisci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…T1rho mapping provides objective information of biochemical components such as glycosaminoglycan, collagen, and water in cartilaginous tissues . We recently demonstrated a positive correlation between the T1rho value and histological scores in the torn meniscus of pigs . T1rho mapping might be one of the methods to quantify the quality of the regenerated meniscus and articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T1rho mapping provides objective information of biochemical components such as glycosaminoglycan, collagen, and water in cartilaginous tissues . We recently demonstrated a positive correlation between the T1rho value and histological scores in the torn meniscus of pigs . T1rho mapping might be one of the methods to quantify the quality of the regenerated meniscus and articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of MRI analysis was performed for the regenerated meniscus and the cartilage of the medial femoral condyle using the sagittal T1 rho mapping. The T1 rho values were calculated with Ziostation2 software (Ziosoft, Tokyo, Japan) …”
Section: Methodsmentioning
confidence: 99%
“…Harteveld et al (2016) and Van Der Kolk et al (2015) manually matched histological sections to their corresponding MR planes using the marked locations from fiducials in the MR images, ink markings in the histologic sections, and gross morphologic features. Nakagawa et al (2016) visually identified the histological sections that were morphologically close to the T 1ρ mapping image, and only those were stained. Koh et al (2016) compared the tissue sections of the largest cut surface of the tumour side-by-side with MR imaging.…”
Section: Slice-to-slice Approaches (2d-2d)mentioning
confidence: 99%
“…Semi-thin sections at 1 μm were collected on glass slides and stained for 30 seconds with Toluidine Blue and then examined by a light microscope. Ultrathin sections at 90 nm were collected on copper grids, double-stained with uranyl acetate and lead citrate, and then examined by transmission electron microscopy (H-7100, Hitachi, Tokyo, Japan) [ 40 ].…”
Section: Methodsmentioning
confidence: 99%